PENCARIAN INFORMASI DATA PESAWAT MENGGUNAKAN NOMOR REGISTRASI PESAWAT DENGAN MEMANFAATKAN DATABASE DAN JSON - Yulis Robert Latumaone; Haruno Sajati; Nurcahyani Dewi Retnowati (Compiler, 2016)
Currently, not much o f public didn’t know about the information of data aircraft, the manufacture and type is sample. The aircraft also has registration number which not same between one aircraft with another aircraft. Information retrival of data aircraft can used registrationnumber with developed in an applicationwith take advantage of database and JSON (JavaScript Object Notation). JSON is a data exchange system that ’s easily translated in to the language o f computer or human. Data exchange these give mean make the distribution application base o f webservices. Web services is a system that provide service the another system to share resource. Procces o f made an application with base of web services must suitable with SOA (Service Oriented Architecture), where SOA is a model representation to up model shape which hasdistribution. For Implementation SOA, it can use the language of programming PHP (Hypertext Preprocessor). Tested on six aircraft, indicated o f airport and airline data can to point out that use of database and JSON can be run well. Decided o f internet network is an obtacle to present data.